A CROSS-SECTIONAL STUDY TO ASSESS THE KNOWLEDGE ATTITUDE PRACTICE OF PHARMACOVIGILANCE AMONG THE DENTISTS IN AN INDIAN TERTIARY CARE TEACHING DENTAL HOSPITAL IN SOUTH INDIA - Pokala, Naveen; Sayeli, VijayKumar; Rayam, Sriharsha (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of the study are to assess the knowledge, attitude, and practices (KAP) about pharmacovigilance in interns, postgraduates, and faculty in a tertiary care teaching dental hospital. Methods: A self-governed KAP survey questionnaire was conducted among interns, postgraduates, and faculty in a tertiary care teaching dental hospital. The KAP questionnaire consists of a total of 20 questions about pharmacovigilance. Results: A total of 58 interns, 26 postgraduates, and 42 faculties have participated in this study. Question 1 inquired about the definition of pharmacovigilance and 31 (53.45%) interns, 20 (76.92%) postgraduates, and 34 (80.95%) faculty were given correct responses. Question 11 queried about the WHO online database for reporting adverse drug reactions (ADRs). Response rates for Question 11 from interns were 20 (34.48%), postgraduates were 15 (57.69%), and faculty was 26 (61.90%). Question 20 quizzed regarding training on how to report ADRs in which 22 (37.93%) interns, 24 (92.30%) postgraduates, and 42 (100%) faculty stated that they were trained on how to report ADR. Conclusion: The majority of interns, postgraduates, and faculty had good knowledge, attitude, and practice about pharmacovigilance. Comparatively, faculty had more knowledge, attitude, and practice about pharmacovigilance among interns, postgraduates, and faculty. Prime reasons for underreporting ADR were a shortage of time to report and the difficulty to conclude whether ADR has occurred or not.